Foreign Assistance and Self-Help: A Reappraisal of Development Finance - Fei, John C. H.; Paauw, Douglas S. (The Review of Economics and Statistics, 1965)
IT is generally believed that foreign capital inflows play a strategic role in promoting progress toward self-sustained growth in developing countries. Yet the relationship between the two has received little rigorous analysis in the voluminous literature on economic development. The Foreign Assistance Act of 1961 enunciated the criterion of as a condition for United States foreign aid,' but the appealing self-help shibboleth has not been given analytical content. However, in a pioneering effort, Professor Rosenstein-Rodan recently raised some of the important analytical questions associated with the self-help notion: